2021
DOI: 10.3390/jcm10214824
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genotoxicity of Hepatitis C Treatment among People Who Inject Drugs

Abstract: Antiviral nucleoside analogues (ANA) are newly used therapeutics acting against the hepatitis C virus (HCV). This class of drug is well known to exhibit toxicity on mitochondrial DNA (mtDNA). People who inject drugs (PWID) are particularly affected by HCV infection and cumulated mitotoxic drug exposure from HIV treatments (antiretrovirals, ARV) and other illicit drugs. This study aims to explore the impact of direct-acting antiviral (DAA) treatments on mtDNA among PWID. A total of 470 actively injecting heroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Several variables may contribute to mitochondrial dysfunction during HCV infection. For instance, DAA therapies target HCV via inhibiting the viral protease or polymerases; however, evidence has suggested that they also inhibit the function of cellular DNA polymerases, including DNA polymerase gamma (Polg), which is critical for replication of the mitochondrial genome (63)(64)(65). In this study, our HCV patients were all DAA-treatment naïve, suggesting that our observations of reduced mtDNA content in our cohort was primarily due to the HCV infection.…”
Section: Discussionmentioning
confidence: 77%
“…Several variables may contribute to mitochondrial dysfunction during HCV infection. For instance, DAA therapies target HCV via inhibiting the viral protease or polymerases; however, evidence has suggested that they also inhibit the function of cellular DNA polymerases, including DNA polymerase gamma (Polg), which is critical for replication of the mitochondrial genome (63)(64)(65). In this study, our HCV patients were all DAA-treatment naïve, suggesting that our observations of reduced mtDNA content in our cohort was primarily due to the HCV infection.…”
Section: Discussionmentioning
confidence: 77%
“…A detailed description of the assays has previously been published [ 8 ]. Succinctly, blood samples were collected on dried blood spot cards (DBS, WhatmanTM 903, GE Healthcare Bio-Sciences Corp.) and DNA was extracted using QIAamp DNA Mini kit (Qiagen, Courtaboeuf, France).…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of MDD was obtained by relative quantification of two qPCRs (2 -ΔΔCt method), one targeting the region which encompasses more than 85% of the known mtDNA deletions and one targeting a very constant region, using DNA extracted from plasma-rich platelets as a calibrator. The MDD rate is the ratio of mutated mtDNA to total mtDNA and is expressed as a percentage [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations